Exploring the mathematical knowledge of prospective elementary teachers in Iceland using the MKT measures - Jóhannsdóttir, Björg; Gísladóttir, Berglind (NOMAD Nordic Studies in Mathematics Education, 2014)
This article reports findings from a study carried out with prospective teachers at the University of Iceland. The study explores the mathematical content knowledge of participants, with a special focus on the understanding of numbers, operations, patterns, functions, and algebra. The mathematical knowledge is measured with interviews and a survey, translated and adapted from the MKT measures designed by Ball and the research team at the University of Michigan. The findings indicate that prospective teachers’ knowledge is procedural and related to the ”standard algorithms” they learned and used in elementary school. Findings also indicate that prospective teachers have difficulty evaluating alternative solution methods, and working with and understanding fractions.